Upcycling of polyurethane waste by mechanochemistry: synthesis of N-doped porous carbon materials for supercapacitor applications - Christina Schneidermann; Pascal Otto; Desirée Leistenschneider; Sven Grätz; Claudia Eßbach; Lars Borchardt (Beilstein Journal of Nanotechnology, 2019)
We developed an upcycling process of polyurethane obtaining porous nitrogen-doped carbon materials that were applied in supercapacitor electrodes. In detail, a mechanochemical solvent-free one-pot synthesis is used and combined with a thermal treatment. Polyurethane is an ideal precursor already containing nitrogen in its backbone, yielding nitrogen-doped porous carbon materials with N content values of 1–8 wt %, high specific surface area values of up to 2150 m2·g−1 (at a N content of 1.6 wt %) and large pore volume values of up to 0.9 cm3·g−1. The materials were tested as electrodes for supercapacitors in aqueous 1 M Li2SO4 electrolyte (100 F·g−1), organic 1 M TEA-BF4 (ACN, 83 F·g−1) and EMIM-BF4 (70 F·g−1).